2022
DOI: 10.1371/journal.pone.0274782
|View full text |Cite
|
Sign up to set email alerts
|

Hematological parameters in a population of male bakers exposed to high heat work environment

Abstract: Objectives The aim of this study was to determine the hematological changes associated with heat exposure in a population of bakers. Materials and methods Personal information was collected using a questionnaire, and a venous blood sample was drawn at the end of a work shift from the bakers and from a control group. The average wet-bulb globe temperature (WBGT) index was measured in the workplaces of both the bakers and the controls. Results This cross-sectional study involved 137 bakers working in 20 bake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
2
6
2
Order By: Relevance
“…In this study, the RBC was high (6.708 ± 2.08) compared to (5.46 ± 1.12) of the control group. The HB was found to be moderate (15.53 ± 2.24) compared to (15.31 ± 1.82) of the control group, the mean ± SD for the PCV was also found to be high (47.597 ± 5.29) compared to (44.02 ± 6.42) of the control subject, this study disagrees with the studies of [ 17 ] and [ 18 ] which reported lower values of RBC, HB, and PCV. In hot climates when humans are exposed to high ambient temperatures, haemo-concentrations are developed due to dehydration, asphyxia, or excitement, causing the release of erythrocytes in the spleen which can result in abnormally higher PCV levels, on the other hand, some authors [ 19 ] reported that season did not affect the Hb concentration.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study, the RBC was high (6.708 ± 2.08) compared to (5.46 ± 1.12) of the control group. The HB was found to be moderate (15.53 ± 2.24) compared to (15.31 ± 1.82) of the control group, the mean ± SD for the PCV was also found to be high (47.597 ± 5.29) compared to (44.02 ± 6.42) of the control subject, this study disagrees with the studies of [ 17 ] and [ 18 ] which reported lower values of RBC, HB, and PCV. In hot climates when humans are exposed to high ambient temperatures, haemo-concentrations are developed due to dehydration, asphyxia, or excitement, causing the release of erythrocytes in the spleen which can result in abnormally higher PCV levels, on the other hand, some authors [ 19 ] reported that season did not affect the Hb concentration.…”
Section: Discussioncontrasting
confidence: 99%
“…The MCV, MCH, and MCHC were found to be high 80.940 ± 11.64, 39.762 ± 7.92, and 42.683 ± 8.64 respectively, compared to 82.59 ± 6.18, 30.12 ± 4.66, and 36.98 ± 2.38 of the control group respectively, this study aligned with the study of [ 17 ] who also found high MCV, MCH, and MCHC among heat-stressed bakery workers. This study observed the mean ± SD for the Platelet to be high (581.43 ± 9439) compared to (460.40 ± 154.90) of the control population, this study disagrees with the study of [ 18 ] who found low platelet value among bakery workers exposed to heat stress. The observation is compatible with a prior study showing that individual differences in platelet concentration persist (Hoareau et al, 2014).…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Specifically, exposure to heat waves increased both HB and PLT levels, while exposure to cold spells increased HB levels and decreased PLT levels. Consistent with our study, previous studies have shown that exposure to hot environments can increase PLT, RBC, and plasma viscosity [ 41 ], while Al-Otaibi et al [ 42 ] observed significantly abnormal HB and PLT levels among individuals working in high-temperature environments compared to those in the control group. From a clinical perspective, these alterations in HB and PLT levels may reflect the body’s adaptation and regulation to extreme temperatures.…”
Section: Discussionsupporting
confidence: 92%